Sosialisasi Membangun Kesadaran Komunikasi Politik melalui Poster untuk Meningkatkan Partisipasi Demokrasi Masyarakat Desa Ileboli - Ina Bili, Destriani A.; Bello, Maria Florencia Yunita; Molan, Kristuanus Simon H. (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of democracy in Indonesia requires the active participation of all layers of society; however, the low level of political communication awareness poses a major obstacle to achieving quality democratic participation, especially at the village level. This community service aims to increase political communication awareness and democratic participation among the people of Ileboli Village, Nagawutung Subdistrict, Lembata Regency, through the use of poster media. The research method employed interviews and direct observation of eligible voters aged 17 and above. The socialization event held on May 14, 2025, at the Ileboli village office hall demonstrated that posters with attractive visual designs and simple language effectively enhanced the community’s knowledge and awareness regarding their rights, obligations, and the importance of involvement in the local democratic process. As a result, political participation among the community began to increase despite initially low levels of knowledge. In conclusion, posters as a political communication medium are a strategic tool to strengthen democratic participation at the village level. It is recommended to develop more varied socialization media and encourage broader community participation to sustainably improve political awareness.